2022
DOI: 10.18267/j.aip.166
|View full text |Cite
|
Sign up to set email alerts
|

Body Image Esteem and Photo Manipulation Among Social Media Users

Abstract: When interacting with each other virtually on social media sites, users may potentially encounter their own "self-presence". To improve their physical self-presence on social media, users might resolve to curate themselves to match their ideal perceptions of themselves and others. This study examines the intention to alter one's factual self in real life whilst contemplating the on-line self on social media. Data were derived from a social survey of Vietnamese adults. The results indicate the remarkable mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
2
0
1
Order By: Relevance
“…Such videos provide excellent opportunities to communicate their popularity and to influence. Pham et al (2021) found that individuals in these videos curate self-image presentations to meet ideal perceptions of themselves and their virtual peers. Self-esteem and social media usage can have a strong relationship (Andreassen et al, 2017).…”
Section: Micro-celebrity and Paths Of Making Body Publicmentioning
confidence: 96%
See 1 more Smart Citation
“…Such videos provide excellent opportunities to communicate their popularity and to influence. Pham et al (2021) found that individuals in these videos curate self-image presentations to meet ideal perceptions of themselves and their virtual peers. Self-esteem and social media usage can have a strong relationship (Andreassen et al, 2017).…”
Section: Micro-celebrity and Paths Of Making Body Publicmentioning
confidence: 96%
“…Self-esteem and social media usage can have a strong relationship (Andreassen et al, 2017). Users with poor self-esteem are more likely to be exploited in the virtual world (Pham et al, 2021). The excessive use of social networking sites is combined with narcissist tendencies.…”
Section: Micro-celebrity and Paths Of Making Body Publicmentioning
confidence: 99%
“…Det normative i normalitetsbegrebet efterlader dog et stort spørgsmål, når det kommer til symptomer på psykiske lidelser -hvad regner vi egentlig for normalt? Både børn og unge spejler sig i deres jaevnaldrende kammerater og i opslag og profiler på sociale medier, og det skaber mistrivsel (Pham et al 2021;Shannon et al 2022). Det betyder, at der som altid, vil vaere trends, der definerer normer og vaerdier blandt gruppen, og som hele tiden aendres.…”
Section: Alexandra Brandt Ryborg Jønsson and John Brandt Brodersen Hv...unclassified
“…In a longitudinal study conducted with adolescents, the frequency of editing their selfies was determined to be linked to an increase in facial and body dissatisfaction six months later (Wang et al 2021). In another study, it was observed that women who edited their photos before sharing them mostly displayed body image dissatisfaction, and there was an association between self-image manipulation and high body anxiety (Pham et al 2022). In another study, it was identified that adolescents, particularly girls, who extensively use social media during adolescence are not satisfied with their bodies.…”
Section: Introductionmentioning
confidence: 99%